Representasi Budaya Barat dalam Cerpen Terjemahan "Nihon No Kotowaza" dalam Perspektif Pascakolonial - Aditya Firmansyah; Diana Puspitasari; Yudi Suryadi (Haluan Sastra Budaya, 2024)
This study examines the representation of the Western world displayed in the daily lives of Japanese people through the character Aku, an Indonesian man who once lived in Europe. This study aims to describe the forms of representation of the Western world carried out by the character Aku so that there will be an effort to internalize Western culture in his life. This research is a descriptive qualitative study with a literature review method using Edward Said's post-colonial perspective. The data collection technique uses reading and note-taking techniques. The object of this research is a translated short story entitled Nihon no Kotowaza which was translated in 2022. The results of the study revealed that indications of the habits of the character Aku who often incorporated Western culture into the life of a Japanese female character, such as watching Western films, watching baseball, drinking beer with American soldiers, and often playing Western songs. That was done because the character Aku was accustomed to life in Europe, so when he was in Japan, these habits were carried over and he tried to incorporate the culture into his close female friends. The internalization of Western culture towards female characters gradually influenced the habits of Japanese women in carrying out their daily lives, although it did not eliminate their original identities. This made female characters carry out two cultures at once in their lives. Based on the study's results, it can be concluded that Western culture has become part of Japanese culture itself. Western cultural customs that are accepted and implemented in society are a form of negotiation between the West and the East.